Global role of IGF2BP1 in controlling the expression of Wnt/β-catenin-regulated genes in colorectal cancer cells - Singh, Vikash; Walter, Vonn; Elcheva, Irina; Imamura Kawasawa, Yuka; Spiegelman, Vladimir S. (Frontiers in Cell and Developmental Biology, 2023)
Wnt/β-catenin signaling controls cell division and lineage specification during embryonic development, and is crucial for stem cells maintenance and gut tissue regeneration in adults. Aberrant activation of Wnt/β-catenin signaling is also essential for pathogenesis of a variety of malignancies. The RNA-binding protein IGF2BP1 is a transcriptional target of Wnt/β-catenin signaling, normally expressed during development and often reactivated in cancer cells, where it regulates stability of oncogenic mRNA. This study aimed to determine the role of IGF2BP1 in post-transcriptional regulation of Wnt/β-catenin-induced genes on a global level in colorectal cancer (CRC) cells, characterized by constitutively active Wnt/β-catenin signaling. In our study, we show that, in contrast to normal cells, CRC cells exhibit a much stronger dependency on IGF2BP1 expression for Wnt/βcatenin-regulated genes. We show that both untransformed and CRC cells have their unique subsets of Wnt/β-catenin -regulated genes that IGF2BP1 directly controls through binding to their mRNA. Our iCLIP analysis revealed a significant change in the IGF2BP1-binding sites throughout the target transcriptomes and a significant change in the enrichment of 6-mer motifs associated with IGF2BP1 binding in response to Wnt/β-catenin signaling. Our study also revealed a signature of IGF2BP1regulated genes that are significantly associated with colon cancer-free survival in humans, as well as potential targets for CRC treatment. Overall, this study highlights the complex and context-dependent regulation of Wnt/β-catenin signaling target genes by IGF2BP1 in non-transformed and CRC cells and identifies potential targets for colon cancer treatment.